In Vitro Synergism of Colistin and N-acetylcysteine against Stenotrophomonas maltophilia - Ciacci, Nagaia (Antibiotics (Basel), 2019)
Stenotrophomonas maltophilia is an emerging global opportunistic pathogen, responsible for a wide range of human infections, including respiratory tract infections. Intrinsic multidrug resistance and propensity to form biofilms make S. maltophilia infections recalcitrant to treatment. Colistin is among the second-line options in case of difficult-to-treat S. maltophilia infections, with the advantage of being also administrable by nebulization. We investigated the potential synergism of colistin in combination with N-acetylcysteine (NAC) (a mucolytic agent with antioxidant and anti-inflammatory properties) against S. maltophilia grown in planktonic phase and biofilm. Eighteen S. maltophilia clinical isolates (comprising three isolates from cystic fibrosis (CF) and two trimethoprim-sulfamethoxazole (SXT)-resistant strains) were included. Checkerboard assays showed a synergism of colistin/NAC combinations against the strains with colistin Minimum Inhibitory Concentration (MIC) >2 µg/mL (n = 13), suggesting that NAC could antagonize the mechanisms involved in colistin resistance. Nonetheless, time–kill assays revealed that NAC might potentiate colistin activity also in case of lower colistin MICs. A dose-dependent potentiation of colistin activity by NAC was also clearly observed against S. maltophilia biofilms, also at sub-MIC concentrations. Colistin/NAC combinations, at concentrations likely achievable by topical administration, might represent a valid option for the treatment of S. maltophilia respiratory infections and should be examined further.